3D COMPUTATIONAL ANALYSIS OF THERMAL&HYDRAULIC PERFORMANCE OF LOUVERED FIN HEAT EXCHANGER WITH VARIABLE LOUVER ANGLE AND LOUVER PITCH - Okbaz, Abdulkerim; Pinarbasi, Ali; Olcay, Ali Bahadir (AMER SOC MECHANICAL ENGINEERS, 2017)
In the present study, 3-D numerical simulations on heat and fluid flow characteristics of double-row multi-louvered fins heat exchanger are carried out. The heat transfer improvement and the corresponding pressure drop amounts were investigated depending on louver angles in the range of 20 degrees <=theta <= 30 degrees, louver pitches of Lp=2,7mm, 3,5mm and 3,8mm and frontal velocities of U-in between 1.22 m/s and 3 m/s. The results are reported in terms of Colburn j-factor, Fanning friction factor f and area goodness factor j/f based on louver angle, louver pitch and Reynolds number. To understand local behavior of flow around louvered fins and heat exchanger tubes, flow visualization results of velocity vectors and stream-lines with temperature counters are presented. It is investigated that increasing louver angle enhances convective heat transfer while hydraulic performance decreases due to increased pressure drop. The flow noticeably behaves louver directed for all louver angles The flow can easily travel between different fins. This case study has been done to design and manufacture an industrial louver fin heat exchanger.
Keywords: FLOW; Engineering